Strategi Pembelajaran Pada Mata Pelajaran Fikih Dalam Mengenalkan Hukum Islam di Madrasah Ibtidaiyah - Azhar, Ihsan Satrya; Fuadi, Ahmad; Dawi, Muhammad Nuh (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
Fiqh learning at the elementary madrasah level has a strategic role in shaping students' basic understanding of Islamic law and in instilling religious values ​​from an early age. However, in practice, many teachers experience obstacles in determining the right learning strategy so that fiqh material can be effectively accepted by students who are still at the concrete development stage. This study aims to describe and analyze learning strategies in fiqh subjects in introducing Islamic law at Bidayatul Hidayah Elementary Madrasah. This study uses a qualitative approach with a phenomenological method. Data were obtained through observation, in-depth interviews, and documentation studies, with primary data sources being teachers and students, and secondary data in the form of learning documents. The data analysis technique follows the Miles and Huberman model, and the validity of the data is tested through triangulation and member checks. The results of the study indicate that the learning strategies used by teachers include direct practice, discussion, demonstration, and contextual approaches that link fiqh material to students' daily lives. Learning planning has been well prepared, but its implementation still faces obstacles such as limited media, time, and differences in student abilities. This study also found the integration of local cultural values ​​in fiqh learning that strengthens students' understanding of Islamic law. The implications of this study are the importance of strengthening teacher competence in implementing active and contextual learning strategies, as well as the need for support for facilities and curriculum that are responsive to the needs of students at the elementary madrasah level.